2003
DOI: 10.1046/j.1440-1681.2003.03906.x
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone prevents cardiac collagen proliferation after myocardial infarction in rats

Abstract: 1. Aldosterone has been considered a key hormone in the regulation of water, sodium and potassium metabolism, thus influencing blood pressure regulation. More recently, several studies have demonstrated that aldosterone is also produced in extra-adrenal tissues (e.g. the heart), suggesting a paracrine effect for aldosterone, such as to increase collagen synthesis in the heart. 2. Because aldosterone production in the heart increases after myocardial infarction (MI), we investigated the effect of chronic admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…For this reason, this model is ideal for the study of therapeutic interventions to minimize the morphological and functional alterations that can occur after the infarction. Thus, many of the interventions used in infarction patients were initially analyzed in the rat model, such as: angiotensinconverting enzyme inhibitors 14,41 , angiotensin-II receptor antagonists 72 , aldosterone antagonists 73 and betablockers 74 .…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, this model is ideal for the study of therapeutic interventions to minimize the morphological and functional alterations that can occur after the infarction. Thus, many of the interventions used in infarction patients were initially analyzed in the rat model, such as: angiotensinconverting enzyme inhibitors 14,41 , angiotensin-II receptor antagonists 72 , aldosterone antagonists 73 and betablockers 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone antagonists demonstrate indirect effects on MMP activity and collagen deposition post-MI. Spironolactone prevents cardiac collagen deposition post-MI in rodents [120]. Spironolactone and hydrochlorothiazide both demonstrated an ability to reduce vascular MMP-2 activity and expression in a model of renovascular hypertension [121].…”
Section: Aldosterone Antagonists-aldosteronementioning
confidence: 99%
“…Expression of CTGF, another profibrotic factor that is also involved in collagen deposition in infarcted hearts, increases in non-infarcted myocardium during injury healing (15). Due to activation of this cytokine cascade, considerable collagen deposition can be observed in infarcted and non-infarcted areas as early as 3 days after MI, which increases during the following 28 days (16,17). Regarding the importance of extracellular matrix remodeling in cardiac dysfunction, Baicu et al (18) showed that isolated papillary muscles exhibit impaired systolic performance if fibrillar collagen is degraded in a timely manner (18).…”
Section: Extracellular Matrix Remodelingmentioning
confidence: 99%
“…Mill et al (17) showed that aldosterone also contributes to increased collagen deposition in non-infarcted viable tissue. Another effect of aldosterone observed in infarcted rats showed that immediate treatment with eplerenone, a selective aldosterone antagonist, improved left ventricular function and reduced deleterious effects of cardiac remodeling by modulation of inflammatory response in acute phase of the healing process (36).…”
Section: The Cardiac Renin-angiotensin-aldosterone Systemmentioning
confidence: 99%